Legal and Regulatory Challenges in the Implementation of the African Continental Free Trade Area Agreement Protocol on Trade in Services in Mozambique - Kabre, Rimdolmsom (University of Pretoria, 2021)
Mini dissertation (LLM (International Trade and Investment Law in Africa))--University of Pretoria, 2021.